2021
DOI: 10.1007/s00464-021-08519-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective cleaning of endoscopic lenses to achieve visual clarity for minimally invasive abdominopelvic surgery: a systematic review

Abstract: Objective To review the recently available interventions to achieve optimal visual clarity in laparoscopic abdominopelvic surgery compared to conventional cleaning alternatives. Summary background data Currently, there is no consensus on the most effective method for the cleaning of endoscopic lenses used in minimally invasive abdominopelvic surgery. Methods Literature searching for articles relevant to answering a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There appears to be limited research focusing on the consequences of lens occlusions and poor visualization in the RAS [13,14] Nezhat's et al found that maintenance of visual clarity is more di cult for RAS because the system occasionally switches between the 30 degree and 0 degree camera, both of which are also bulkier than the laparoscopic camera [7]. FloShield™ (Minimally Invasive Devices, Inc.) introduced a cleaner speci cally designed for the robotic scope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be limited research focusing on the consequences of lens occlusions and poor visualization in the RAS [13,14] Nezhat's et al found that maintenance of visual clarity is more di cult for RAS because the system occasionally switches between the 30 degree and 0 degree camera, both of which are also bulkier than the laparoscopic camera [7]. FloShield™ (Minimally Invasive Devices, Inc.) introduced a cleaner speci cally designed for the robotic scope.…”
Section: Introductionmentioning
confidence: 99%
“…FloShield™ (Minimally Invasive Devices, Inc.) introduced a cleaner speci cally designed for the robotic scope. Moreover, Insu ow™ (Lexion Medical) has tested their device in some RAS cases [5,7] However, such solutions have shown limited clinical impact and more research needs to be conducted to understand and quantify how visual occlusions play a role in the outcome of an RAS procedure [14]. In order to shed a light on the degree of surgical disruption, this study quanti es the degree of disruption due to visual acuity in RAS at a major academic institution.…”
Section: Introductionmentioning
confidence: 99%